THE EFFECTIVENESS OF ARTIFICIAL INTELLIGENCE ON THE WORKFORCES IN SAUDI ARABIA ORGANISATIONS - Alanizan, Salem (International Journal For Research In Business, Management And Accounting, 2024)
Artificial intelligence (AI) has swiftly permeated various sectors, impacting human activities such as transportation, production, and manufacturing. This study assesses the potential influence of AI on employment in Saudi Arabia, utilizing a quantitative cross-sectional approach with a sample of 300 employees from diverse sectors. Employing inferential and descriptive statistics, the research indicates a positive moderate effect of AI on future employment. The findings provide valuable insights for research and development (R&D) and managerial decisions, aiding in navigating the labour market landscape.